Remotely supervised internship: between impasses or possibilities - Silva, Maria Clarice da (2021)
The supervised internship is considered the moment when learned theories are combined with practice. His interest in the subject came from his experience as a teacher of the supervised internship discipline in the biological sciences course at the Regional University of Cariri-URCA Decentralized Unit of Campos Sales-Ce. To proceed with this research, questions were asked such as: Will the internship remotely allow students to have a dimension of teaching practice? Are schools prepared to receive intern students in remote format? This research aims to present reflections about the internship remotely, we want to understand the current context caused by the worldwide pandemic of Covid-19 in the educational area and to know the experiences of remote teaching and its impacts on education. As a methodological procedure, we opted for the bibliographical survey and report of the experience in the discipline. We conclude that remote teaching fragments the practice of trainees in the exercise of initial teaching practice.